ASSESSMENT AND RECOMMENDATIONS ON THE IMPLEMENTATION OF TAHFIZ INTEGRATED CURRICULUM (KBT) - Saiful Rafizan Jamil; Mohamad Khairi Haji Othman (INTERNATIONAL JOURNAL OF MODERN EDUCATION (IJMOE), 2024)
Tahfiz Integrated Curriculum (KBT) is one of the tahfiz education approaches applied in Malaysia. Tahfiz education now emphasizes learning that integrates tahfiz and academic lessons into one curriculum. The combination of Quranic, Ijtihadik and Encyclopaedic elements is the central core of Tahfiz Model Ulul Albab (TMUA), which was implemented as early as 2014 until now. Thus, the question arises regarding how effective and successful this curriculum produces Huffaz as planned. Accordingly, this paper will cover the Tahfiz Integrated Curriculum (KBT) and curriculum evaluation as well as curriculum evaluation models. Finally, some methods of integration and evaluation of the tahfiz integrated curriculum are also proposed to ensure tahfiz learning is effective. The implications of this study guide the authorities to formulate strategies to maximize the excellence of the huffaz.